Surrogate to predict overall survival in patients with BRAF V600E-mutant colorectal cancer treated with BRAF inhibitor combinations - J. Ros; V. Navarro; G. Villacampa; I. Baraibar; F. Salvà; M. Rodriguez; C. Vaghi; A. Garcia; A. Alcaraz; J. Tabernero; E. Élez; R. Dienstmann (ESMO Gastrointestinal Oncology)
Background: The BRAF V600E mutation, found in up to 12% of patients with metastatic colorectal cancer, is associated with aggressive disease and poor response to standard chemotherapy. However, the advent of BRAF inhibitors has led to improved clinical outcomes and survival. While surrogate endpoints for predicting overall survival (OS) have been extensively studied in the overall colorectal cancer population treated with chemotherapy, their applicability in patients with BRAF V600E-mutant colorectal cancer receiving either BRAF inhibitor combinations or conventional chemotherapy remains unclear, and needs to be better elucidated. The aim of the study was to evaluate surrogate endpoints to predict OS in patients with BRAF V600E-mutant colorectal cancer treated with either BRAF inhibitor combinations or chemotherapy. Materials and methods: A systematic review was carried out to identify clinical trials or real-world cohorts evaluating patients with BRAF-mutant colorectal cancer treated either with chemotherapy or BRAF inhibitor combinations. A control cohort of melanoma patients treated with BRAF inhibitors in a phase III randomized trial was included. Adjusted R2 (R2adj) values were calculated to quantify the association between surrogate endpoints and median OS. Results: Overall, a total of 5227 patients included in 29 cohorts were analyzed. Among patients with colorectal cancer treated with chemotherapy, overall response rate (ORR) and disease control rate (DCR) showed a high correlation with OS (R2adj > 0.90). Among patients treated with targeted therapy, progression-free survival (PFS) showed the highest correlation with OS (R2adj = 0.90). In the melanoma cohort, PFS was strongly associated with OS (R2adj = 0.92). Conclusions: In BRAF-mutant colorectal cancer, standard surrogate endpoints for chemotherapy-based treatments accurately predict OS; however, when patients are treated with targeted therapies, both ORR and PFS have proven to be reliable predictors of survival.